Feto-fetal transfusion syndrome - Siusiuka, V. H.; Bohuslavska, N.; Babinchuk, O.; Deinichenko, O. V.; Onopchenko, S. P.; Сюсюка, Володимир Григорович; Дейніченко, Олена Валеріївна; Онопченко, Світлана Павлівна (My University, 2024)
Feto-fetal transfusion syndrome – Twin-to-Twin Transfusion Syndrome (FFTS) is a specific complication of multiple pregnancy (MP), which is diagnosed in 10-20% of monochorionic MP.
Keywords: тези доповідей